Overflow type high-flux water treatment photocatalytic sterilization material as well as preparation method and application thereof
By using heterogeneous photocatalytic materials of CuO/Ag2S/Ag3PO4 composite materials in the water sterilization module, combined with a low-power UV light source, the problem of poor sterilization effect under large flow is solved, and an efficient, safe and low-cost sterilization effect of water sterilization is achieved.
Patent Information
- Application Number
- CN202411830214.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-25
AI Technical Summary
The existing water sterilization module has poor sterilization effect under large flow, large equipment size and high operating costs, and photocatalytic materials are prone to fall off under large flow, which poses safety hazards.
CuO/Ag2S/Ag3PO4 composite material is used to grow copper oxide nanoarrays in situ through a copper mesh, and irregular Ag3PO4 particles and fine Ag2S microspheres are embedded to form a heterogeneous photocatalytic material with a core-shell structure, and combined with a small-power UV light source to form a UV-photocatalytic sterilization module.
The sterilization rate is significantly improved under large flow, with a sterilization rate of more than 97.78%. The material structure reduces pollution and losses, adapts to large flow applications, has high safety and low operating costs.
Smart Images

Figure CN119867082A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of water sterilization, and in particular relates to an over-flow type large-flux water treatment photocatalytic sterilization material and a preparation method and application thereof. Background Art
[0002] Water contains a large number of microorganisms such as bacteria, viruses, and fungi, and water safety has attracted much attention. Currently, water bodies are mainly sterilized and disinfected by using ultraviolet rays, ozone, chlorine, and other chemical agents. Water that has been effectively sterilized and disinfected usually meets national drinking water standards.
[0003] Ultraviolet sterilization technology is a physical method that does not add any substances to the water body and is widely used in the field of water sterilization. At present, most common water sterilization modules are static water sterilization modules. By irradiating the water body with high-intensity and long-life ultraviolet light, the microorganisms in the water body will be directly killed. In some drinking water equipment, it is necessary to sterilize and disinfect water with a certain flow rate at a large flow rate. Fast-flowing water will greatly reduce the contact time between microorganisms and ultraviolet light, resulting in the above-mentioned module The sterilization effect on microorganisms is not ideal.
[0004] At present, the sterilization efficiency is mainly improved by the design of the sterilization module, such as increasing the power of ultraviolet lamp beads, optimizing the sterilization channel, and adding reflective structures. Chinese patent application 202120673698.9 discloses a drinking water device and a flowing water sterilization module, which achieves effective sterilization and disinfection of water bodies with weak light or far from the light source through the emission structure and optimized sterilization path; Chinese patent application 202021794707.1 discloses a large-flow ultraviolet sterilization device, which achieves effective sterilization and disinfection of large flow by adding a return hole inside to connect several sterilization modules in parallel; Chinese patent application 202320177540.1 discloses a large-flow deep ultraviolet water sterilization device, which uses high-power lamp beads and lengthened sterilization waterways, and uses high-reflectivity reflective ultraviolet materials to effectively improve the sterilization rate; but the above method increases the sterilization efficiency while also increasing the volume and operating cost of the equipment.
[0005] In addition, UV synergistic sterilization technology has been developed in the field of water sterilization, including UV-ultrasound, UV-micro-ozone, UV-photocatalysis, etc. UV-photocatalysis technology combines the dual effects of UV sterilization and photocatalytic sterilization, achieving efficient sterilization of flowing water while effectively controlling costs. It is a reliable, effective and cost-effective method.
[0006] Photocatalytic sterilization materials are semiconductor materials with photocatalytic properties. Under the irradiation of light, they can produce active components with strong oxidizing properties, including superoxide free radicals (·O2 - ), hydroxyl radical (·OH), singlet oxygen ( 1O2) and hydrogen peroxide (H2O2) will attack the phospholipids, proteins and peptidoglycan on the bacterial cell wall, oxidize the cell wall and destroy its selective permeability, and then pass through the cell wall to destroy the cell membrane, so that the intracellular substances flow out and cause the bacteria to die. In addition, the active ingredient will oxidize coenzyme A, destroy the normal metabolism of bacteria and cause bacterial death. Chinese patent application 201520303360.9 discloses a treatment device for ultraviolet light catalytic strong oxidation drinking water, which comprehensively utilizes the synergistic effect of ultraviolet sterilization and photocatalytic strong oxidation sterilization to treat drinking water, and realizes efficient sterilization and disinfection of flowing water, but still needs to control the maximum flow rate of the water outlet and the water time of the bottle body. Water and photocatalytic materials need to be repeatedly in contact to achieve the best performance, and the inlet water needs to flow in the device for 10s to obtain product water. Currently, most of the disclosed photocatalytic antibacterial agents are nanopowders or granular materials, which are easy to fall off from the carrier into the water body under large flow rates, posing a health threat to organisms. Therefore, the development of photocatalytic materials suitable for water sterilization under large flow rates has huge market application potential. Summary of the invention
[0007] In view of the shortcomings and deficiencies of existing water sterilization modules, such as poor sterilization effect under large flow rates, large equipment size, high operating costs, and shedding of photocatalytic materials, the primary purpose of the present invention is to provide a method for preparing an over-flow large-flux water treatment photocatalytic sterilization material (a CuO / Ag2S / Ag3PO4 composite material that can cooperate with low-power ultraviolet light for photocatalytic sterilization).
[0008] The CuO / Ag2S / Ag3PO4 heterogeneous photocatalytic material prepared by the present invention is mainly grown by in-situ growth of copper oxide nanoarrays on a copper mesh, so that irregular Ag3PO4 particles are stably embedded in the CuO nanoarray, and finer Ag2S microspheres continue to accumulate on the Ag3PO4 particles to form a structure similar to a core-shell structure, which greatly reduces the pollution and loss caused by the material during use, making it suitable for large-flow application scenarios. The heterogeneous structure composed of CuO and Ag2S / Ag3PO4 can promote the separation of photogenerated electrons and holes, and effectively increase the generation of active free radicals. At the same time, the copper mesh, as a substrate material, can not only grow CuO nanosheet arrays, but also conduct electricity to promote the transfer of photogenerated electrons, accelerate the separation of photogenerated electrons, and effectively inhibit the recombination of photogenerated carriers. Ag2S microspheres deposited on the surface of the material can promote the rapid combination of S atoms in Ag2S with the hydrophilic head of lipids in the cell membrane and the combination of negatively charged phosphate groups of lipid molecules with Ag atoms through the combined action of electrostatic action and van der Waals force, thereby accelerating the death of microorganisms and improving the sterilization effect. The application of the CuO / Ag2S / Ag3PO4 heterogeneous photocatalytic material prepared by the present invention is mainly to form a UV-photocatalyst sterilization module by combining it with a UV-LED module, and to achieve effective sterilization and disinfection of water bodies in coordination with low-power UV at a large flow rate.
[0009] Another object of the present invention is to provide a large-flux water treatment photocatalytic sterilization material prepared by the above preparation method.
[0010] Another object of the present invention is to provide the application of the above-mentioned large-flux water treatment photocatalytic sterilization material in water purification.
[0011] The purpose of the present invention is achieved through the following technical solutions:
[0012] A method for preparing a flow-through large-flux water treatment photocatalytic sterilization material comprises the following steps:
[0013] (1) In situ growth of CuO nanosheet arrays on a copper mesh by oxidation etching to obtain Cu@CuO;
[0014] (2) The Cu@CuO is immersed in a silver nitrate solution and reacted at room temperature for a period of time, and then thiourea and water are added and the reaction is continued at room temperature for a period of time. The intermediate product I is transferred to a reactor for hydrothermal reaction. After cooling, the intermediate product II is immersed in a silver nitrate solution and reacted at room temperature for a period of time. Then, Na2HPO4 solution is added dropwise to the reaction system under light-proof conditions and the heating reaction is continued for a period of time. The reaction is then continued at room temperature for a period of time. Finally, after washing and drying, a CuO / Ag2S / Ag3PO4 heterogeneous photocatalytic material is obtained, i.e., a flow-through large-flux water treatment photocatalytic sterilization material.
[0015] Preferably, the mesh size of the copper mesh in step (1) is ≤200 mesh, more preferably 200 mesh.
[0016] Preferably, the copper mesh in step (1) needs to be soaked in anhydrous ethanol and then cleaned in sequence with hydrochloric acid, acetone, anhydrous ethanol and deionized water.
[0017] More preferably, the concentration of the hydrochloric acid is 0.5 to 1.5 mol / L.
[0018] Preferably, the method for in-situ growth of CuO nanosheet arrays by oxidation etching in step (1) is:
[0019] Ammonium persulfate and sodium hydroxide are dissolved in water to prepare a mixed solution, a copper mesh is immersed in the mixed solution, heated for reaction, washed, and dried to obtain Cu@CuO.
[0020] More preferably, the mass ratio of ammonium persulfate to sodium hydroxide is 1:5-25; more preferably 1:17.
[0021] More preferably, in the mixed solution, the concentration of ammonium persulfate is 6-33 mg / ml; more preferably 6 mg / ml.
[0022] More preferably, the heating reaction is carried out at a temperature of 50 to 80° C. and for a time of 16 to 24 hours.
[0023] Preferably, the concentration of the silver nitrate solution in step (2) is 0.1-0.3 mol / L, and more preferably 0.2 mol / L.
[0024] Preferably, the reaction time of immersing in the silver nitrate solution at room temperature in step (2) is 1.5 to 2.5 hours, more preferably 2 hours.
[0025] Preferably, the reaction speed in step (2) is 50 to 200 r / min; more preferably 50 to 80 r / min.
[0026] Preferably, in the process of preparing the intermediate product I in step (2), the ratio of silver nitrate, thiourea and water is 3-6 mmol: 0.40-1.00 g: 100-200 ml; more preferably 5 mmol: 0.60 g: 100 ml.
[0027] Preferably, the time for adding thiourea and water and continuing the reaction in step (2) is 20 to 40 minutes, more preferably 30 minutes.
[0028] Preferably, the temperature of the hydrothermal reaction in step (2) is 90-120° C. and the time is 2-5 hours.
[0029] Preferably, the ratio of the Cu@CuO in step (2) to the silver nitrate used twice successively is 2g:3-6mmol:5-10mmol; more preferably 2g:5mmol:5mmol.
[0030] Preferably, the concentration of the Na2HPO4 solution in step (2) is 0.15-0.25 mol / L; more preferably 0.2 mol / L.
[0031] Preferably, the ratio of thiourea to Na2HPO4 in step (2) is 0.40-1.00 g:1.8-3.6 mmol; more preferably 0.60 g:1.8 mmol.
[0032] Preferably, in step (2), the temperature for adding the Na2HPO4 solution and continuing to heat the reaction is 40 to 60°C and the time is 1.5 to 3 hours.
[0033] Preferably, the reaction time at room temperature after the dropwise addition of the Na2HPO4 solution in step (2) is 2 to 4 hours.
[0034] Preferably, the washing in step (2) refers to repeated washing with deionized water and anhydrous ethanol; the drying temperature is 60 to 80° C. and the drying time is 8 to 12 hours.
[0035] The above preparation method produces a large-flux water treatment photocatalytic sterilization material.
[0036] The above-mentioned large-flux water treatment photocatalytic sterilization material is used in water purification.
[0037] Preferably, the over-flow large-flux water treatment photocatalytic sterilization material is combined with a UV-LED light source to form a UV-photocatalyst sterilization module to achieve sterilization and purification of flowing water at a large flow rate.
[0038] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0039] (1) The present invention uses copper mesh as the base material, which has the advantages of wide source and low price.
[0040] (2) The CuO / Ag2S / Ag3PO4 heterogeneous photocatalytic material prepared by the present invention has CuO nanosheet arrays, irregular Ag3PO4 particles, and fine Ag2S microspheres grown in situ on the surface of the copper mesh. The core-shell structure formed by the material greatly reduces the pollution and loss caused by the material during use, is suitable for large-flow application scenarios, has no secondary pollution, and is highly safe.
[0041] (3) The CuO / Ag2S / Ag3PO4 heterogeneous photocatalytic material prepared by the present invention has a Z-scheme heterostructure, which effectively promotes the separation of photogenerated carriers of Ag2S / Ag3PO4 and CuO, and the copper mesh of the substrate can conduct photogenerated electrons, effectively increasing the generation of active free radicals and improving the photocatalytic efficiency.
[0042] (4) The CuO / Ag2S / Ag3PO4 heterogeneous photocatalytic material prepared by the present invention has a good bactericidal effect. At a large flow rate of 5.4L / min, in conjunction with a 560mW ultraviolet light source, the bactericidal rate reaches 97.78%; at a large flow rate of 3L / min, in conjunction with an 89.9mW ultraviolet light source, the bactericidal rate reaches 95.91%. When the power is reduced to 40.7mW, the bactericidal rate is still above 90%.
[0043] (5) The method for growing CuO nanosheet arrays adopted in the present invention has mild reaction conditions and is convenient for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a schematic diagram of the application of a high-power UV-photocatalyst sterilization module;
[0045] Among them: 1 is the water inlet; 2 is the UV-LED line group; 3 is the UV-LED lamp bead; 4 is the CuO / Ag2S / Ag3PO4 photocatalyst; 5 is the water outlet.
[0046] Figure 2This is a schematic diagram of the application of a low-power UV-photocatalyst sterilization module;
[0047] Among them: 1 is the water inlet; 2 is the UV-LED line group; 3 is the UV-LED lamp bead; 4 is the fixing screw; 5 is the CuO / Ag2S / Ag3PO4 photocatalyst; 6 is the water outlet.
[0048] Figure 3 The sterilization efficiency diagram of Examples 1 and 2.
[0049] Figure 4 The figure is a graph of the sterilization efficiency of Example 2 and Comparative Examples 1 and 2 under low-power ultraviolet irradiation.
[0050] Figure 5 SEM images of CuO / Ag2S / Ag3PO4 photocatalysts prepared at different concentrations;
[0051] Wherein: (a) is the lower concentration of comparative example 1; (b) is the normal concentration of embodiment 1; (c) is the higher concentration of comparative example 2.
[0052] Figure 6 The XRD diagram of the catalyst in Example 1 before and after use;
[0053] The blue one is before use, and the orange one is after use. DETAILED DESCRIPTION
[0054] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0055] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0056] Example 1
[0057] (1) Cut the 200 mesh copper mesh into 1*5cm 2 The copper mesh was immersed in 1 mol / L HCl solution for 25 min to remove the oxide layer on the surface of the copper mesh, and then ultrasonicated in acetone, ethanol and deionized water for 5 min to remove surface impurities and obtain a clean copper mesh.
[0058] (2) Dissolve 0.193 g of ammonium persulfate in 10 mL of deionized water to obtain solution A. Dissolve 3.2 g of sodium hydroxide in 20 mL of deionized water and cool to room temperature to obtain solution B. Pour solution B into solution A, shake for 10 min, and let stand to obtain solution C.
[0059] (3) Add the cleaned copper mesh to solution C, soak and react at room temperature for 15 minutes, transfer the mixture to a polytetrafluoroethylene-lined reactor, seal it, and treat it at 80°C for 24 hours (in an oven); take out the copper mesh on which the CuO nanosheet array grows after the reaction, rinse it repeatedly with deionized water and ethanol for 3 times; and dry it at 60°C to obtain a Cu@CuO nanosheet array.
[0060] (4) Cu@CuO nanosheet arrays (2.0 g) were added to AgNO3 (25 mL, 0.2 mol / L) solution, and the mixture was placed on a shaker at 50 r / min for 2 h.
[0061] (5) Thiourea (0.60 g) and 100 ml of ultrapure water were added and placed on a shaker at 50 r / min for 30 min. The mixture was then transferred to a polytetrafluoroethylene-lined reactor, sealed, with the filling rate controlled at about 60%, and hydrothermally reacted at 105° C. for 3 h.
[0062] (6) After cooling, the mixture was taken out from the autoclave, and 25 mL of AgNO3 (0.2 mol / L) solution was added; the mixture was placed on a shaker at 80 r / min for 2 h. Under a light-proof environment, 9 mL of Na2HPO4 (0.2 mol / L) solution was added dropwise to the above mixture under continuous shaking, and then kept at 50 °C for 2 h and transferred to a shaker at 80 r / min for 3 h. Finally, the sample was repeatedly washed with deionized water and anhydrous ethanol, and activated in an oven at 80 °C to obtain a CuO / Ag2S / Ag3PO4 photocatalyst.
[0063] (7) Cut out a 10 mm long and 6 mm wide CuO / Ag2S / Ag3PO4 photocatalytic material and fix it at the central axis of the UV-LED module cavity, so that it forms a high-power UV-photocatalyst sterilization module with a high-power UV-LED light source (560 mW).
[0064] (8) The access flow rate was about 5.4 L / min and the total number of colonies was about 9.0×10 3 CFU / mL of Micrococcus luteus (CGMCC1.193, purchased from Guangdong Microbial Culture Collection Center) was spiked into the water channel. The inlet and outlet water of the high-power UV-photocatalyst sterilization module was taken for microbial culture, and the total number of colonies was counted. The test results are shown in Table 1.
[0065] Table 1 Bactericidal effect of Example 1 application
[0066]
[0067] Example 2
[0068] (1) The preparation of CuO / Ag2S / Ag3PO4 heterogeneous photocatalytic material is the same as in Example 1.
[0069] (2) Cut out a 10 mm long and 6 mm wide CuO / Ag2S / Ag3PO4 photocatalytic material and fix it at the central axis of the UV-LED module cavity, so that it forms a low-power UV-photocatalyst sterilization module with a low-power UV-LED light source (89.9 mW, 40.7 mW).
[0070] (3) The access flow rate is about 3L / min, and the total number of colonies is about 4.4×10 4 CFU / mL of Micrococcus luteus (CGMCC1.193, purchased from Guangdong Microbial Culture Collection Center) was spiked into the water channel. The inlet and outlet water of the low-power UV-photocatalyst sterilization module was taken for microbial culture, and the total number of colonies was counted. The test results are shown in Table 2.
[0071] Table 2 Bactericidal effect of Example 2 application
[0072]
[0073] Example 3
[0074] (1) Preparation of CuO / Ag2S / Ag3PO4 heterogeneous photocatalytic materials Refer to Example 1, except that: Step (4) 15 mL of AgNO3 solution, concentration 0.2 mol / L; Step (5) 0.40 g of thiourea; Step (6) 30 mL of AgNO3 solution, concentration 0.2 mol / L, 12 mL of Na2HPO4 solution, concentration 0.2 mol / L.
[0075] (2) The antibacterial effect against Micrococcus luteus (CGMCC1.193, purchased from Guangdong Microbiological Culture Collection Center) was similar to that of Examples 1 and 2.
[0076] Example 4
[0077] (1) Preparation of CuO / Ag2S / Ag3PO4 heterogeneous photocatalytic materials Refer to Example 1, except that: Step (4) 30 mL of AgNO3 solution, concentration 0.2 mol / L; Step (5) 1.00 g of thiourea; Step (6) 50 mL of AgNO3 solution, concentration 0.2 mol / L, 18 mL of Na2HPO4 solution, concentration 0.2 mol / L.
[0078] (2) The antibacterial effect against Micrococcus luteus (CGMCC1.193, purchased from Guangdong Microbiological Culture Collection Center) was similar to that of Examples 1 and 2.
[0079] Comparative Example 1
[0080] (1) The preparation of Cu@CuO nanosheet arrays was the same as in Example 1.
[0081] (2) Cu@CuO nanosheet arrays (2.0 g) were added to AgNO3 (25 mL, 0.05 mol / L), and the mixture was placed on a shaker at 50 r / min for 2 h.
[0082] (3) Thiourea (0.15 g) and 100 ml of ultrapure water were added and placed on a shaker at 50 r / min for 30 min. The mixture was then transferred to a polytetrafluoroethylene-lined reactor, sealed, with the filling rate controlled at about 60%, and hydrothermally reacted at 105° C. for 3 h.
[0083] (4) After cooling, the mixture was taken out from the autoclave, and 25 mL of AgNO3 (0.05 mol / L) was added; the mixture was placed on a shaker at 80 r / min for 2 h. In a light-proof environment, 9 mL of Na2HPO4 (0.05 mol / L) was added to the above mixture under continuous shaking, and then kept at 50 °C for 2 h and transferred to a shaker at 80 r / min for 3 h. Finally, the sample was repeatedly washed with deionized water and anhydrous ethanol, and activated in an oven at 80 °C to obtain a low-concentration CuO / Ag2S / Ag3PO4 photocatalyst.
[0084] (5) Cut out a 10 mm long and 6 mm wide CuO / Ag2S / Ag3PO4 photocatalytic material and fix it at the central axis of the UV-LED module cavity, so that it forms a low-power UV-photocatalyst sterilization module with a low-power UV-LED light source (89.9 mW).
[0085] (6) The access flow rate is about 3L / min, and the total number of colonies is about 4.4×10 4 CFU / mL of Micrococcus luteus (CGMCC1.193, purchased from Guangdong Microbial Culture Collection Center) was spiked into the water channel. The inlet and outlet water of the low-power UV-photocatalyst sterilization module was taken for microbial culture, and the total number of colonies was counted. The test results are shown in Table 3.
[0086] Table 3 Bactericidal effect of comparative example 1
[0087]
[0088] Comparative Example 2
[0089] (1) The preparation of Cu@CuO nanosheet arrays was the same as in Example 1.
[0090] (2) Cu@CuO nanosheet arrays (2.0 g) were added to AgNO3 (25 mL, 0.4 mol / L), and the mixture was placed on a shaker at 50 r / min for 2 h.
[0091] (3) Thiourea (1.20 g) and 100 ml of ultrapure water were added and placed on a shaker at 50 r / min for 30 min. The mixture was then transferred to a polytetrafluoroethylene-lined reactor, sealed, with the filling rate controlled at about 60%, and hydrothermally reacted at 105° C. for 3 h.
[0092] (4) After cooling, the mixture was taken out from the autoclave, and 25 mL of AgNO3 (0.4 mol / L) was added; the mixture was placed on a shaker at 80 r / min for 2 h. In a light-proof environment, 9 mL of Na2HPO4 (0.4 mol / L) was added to the above mixture under continuous shaking, and then kept at 50 °C for 2 h and transferred to a shaker at 80 r / min for 3 h. Finally, the sample was repeatedly washed with deionized water and anhydrous ethanol, and activated in an oven at 80 °C to obtain a high-concentration CuO / Ag2S / Ag3PO4 photocatalyst.
[0093] (5) Cut out a 10 mm long and 6 mm wide CuO / Ag2S / Ag3PO4 photocatalytic material and fix it at the central axis of the UV-LED module cavity, so that it forms a low-power UV-photocatalyst sterilization module with a low-power UV-LED light source (89.9 mW).
[0094] (6) The access flow rate is about 3L / min, and the total number of colonies is about 4.4×10 4 CFU / mL of Micrococcus luteus (CGMCC1.193, purchased from Guangdong Microbial Culture Collection Center) was spiked into the water channel. The inlet and outlet water of the low-power UV-photocatalyst sterilization module was taken for microbial culture, and the total number of colonies was counted. The test results are shown in Table 4.
[0095] Table 4 Bactericidal effect of comparative example 2
[0096]
[0097] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a photocatalytic sterilization material for over-flow high-flux water treatment, characterized in that: The following steps are involved: (1) In situ growth of CuO nanosheet arrays on a copper mesh by oxidation etching to obtain Cu@CuO; (2) The Cu@CuO is immersed in a silver nitrate solution and reacted at room temperature for a period of time, and then thiourea and water are added and the reaction is continued at room temperature for a period of time. The intermediate product I is transferred to a reactor for hydrothermal reaction. After cooling, the intermediate product II is immersed in a silver nitrate solution and reacted at room temperature for a period of time. Then, Na2HPO4 solution is added dropwise to the reaction system under light-proof conditions and the heating reaction is continued for a period of time. The reaction is then continued at room temperature for a period of time. Finally, after washing and drying, a CuO / Ag2S / Ag3PO4 heterogeneous photocatalytic material is obtained, i.e., a flow-through large-flux water treatment photocatalytic sterilization material.
2. The preparation method according to claim 1, characterized in that: The concentration of the silver nitrate solution in step (2) is 0.1-0.3 mol / L; The concentration of the Na2HPO4 solution in step (2) is 0.15-0.25 mol / L.
3. The preparation method according to claim 1 or 2, characterized in that: In the process of preparing the intermediate product I in step (2), the ratio of silver nitrate, thiourea and water is 3-6 mmol: 0.40~1.00g:100~200ml; In step (2), the ratio of Cu@CuO to the silver nitrate used twice is 2 g: 3-6 mmol: 5-10 mmol; The ratio of thiourea to Na2HPO4 in step (2) is 0.40-1.00 g: 1.8-3.6 mmol.
4. The preparation method according to claim 1 or 2, characterized in that: The reaction time of immersing in the silver nitrate solution at room temperature in step (2) is 1.5 to 2.5 hours; The time of adding thiourea and water and continuing the reaction in step (2) is 20 to 40 minutes; The temperature of the hydrothermal reaction in step (2) is 90-120° C. and the time is 2-5 hours; The temperature of adding Na2HPO4 solution and continuing heating the reaction in step (2) is 40-60°C and the time is 1.5-3h; The reaction time at room temperature after the Na2HPO4 solution is added dropwise in step (2) is 2 to 4 hours.
5. The preparation method according to claim 1 or 2, characterized in that: The concentration of the silver nitrate solution in step (2) is 0.2 mol / L; The concentration of the Na2HPO4 solution in step (2) is 0.2 mol / L.
6. The preparation method according to claim 1 or 2, characterized in that: The mesh size of the copper mesh in step (1) is ≤200 mesh; The method for in-situ growth of CuO nanosheet arrays by oxidation etching in step (1) is: Ammonium persulfate and sodium hydroxide are dissolved in water to prepare a mixed solution, a copper mesh is immersed in the mixed solution, heated for reaction, washed, and dried to obtain Cu@CuO.
7. The preparation method according to claim 6, characterized in that: The mass ratio of ammonium persulfate to sodium hydroxide is 1:5-25; In the mixed solution, the concentration of ammonium persulfate is 6-33 mg / ml; The temperature of the heating reaction is 50-80° C. and the time is 16-24 hours.
8. A high-throughput photocatalytic sterilization material for water treatment prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the over-flow type large-flux water treatment photocatalytic sterilization material as described in claim 8 in water purification.
10. The use according to claim 9, characterized in that: The over-flow large-flux water treatment photocatalytic sterilization material is combined with a UV-LED light source to form a UV-photocatalyst sterilization module to achieve sterilization and purification of flowing water at a large flow rate.
Citation Information
Patent Citations
Processing apparatus of strong oxidation drinking water of ultraviolet ray catalysis
CN205045844U
Large-flow ultraviolet sterilization device
CN213834621U
Drinking water equipment and flowing water sterilization module
CN215559143U
Large-flow deep ultraviolet water sterilization device
CN219409351U